Dynamics of Understory Vegetation in Agroforestry and Monoculture Teak (Tectona grandis) Stands during Wet and Dry Seasons - Setiawan, Adi; Kholifah, Izzah Nurul; Ramadhana, Varotama Putra (Plantropica: Journal of Agricultural Science, 2026)
Planting patterns and seasonal variability strongly influence the diversity, dynamics, and species composition of understory vegetation in teak (Tectona grandis), a deciduous tree species. This study aimed to assess species diversity, dynamics, and composition of understory vegetation under agroforestry (AF) and monoculture (MN) teak systems during the wet season (WS) and dry season (DS). Field surveys were conducted in February–March and July–August 2023 in teak production forests managed by Perum Perhutani, Kalipare District, Malang Regency, East Java, Indonesia. A total of 117 systematically distributed 1 × 1 m plots were established, consisting of 27 plots in AF and 90 plots in MN stands, with 5 m spacing between plots. Plot locations were recorded using a Global Positioning System (GPS). Within each plot, understory species composition, percentage cover of vegetation, litter, and bare soil were recorded, and Sørensen similarity indices were calculated. Environmental variables measured included canopy openness and rainfall. Canopy openness was quantified using hemispherical photographs taken at 1 m above ground level with a 360° camera and analyzed using GLA 2.0 software. Rainfall data were obtained from the local climatological station. The results revealed clear differences in understory species composition between AF and MN systems. Monoculture teak stands supported 49 species belonging to 23 families, whereas agroforestry stands contained 35 species from 16 families. Vegetation composition and structure differed substantially between AF and MN systems. Understory diversity in MN stands during the dry season was higher than in AF stands, likely because agroforestry practices in the study area resemble intensive monoculture of annual crops. Canopy openness and rainfall were identified as significant drivers influencing understory vegetation cover.